Health, Economics and Ancient Greek Medicine - Carl Hampus Lyttkens (Lund University, School of Economics and Management, Department of Economics, 2011)
A period of two and a half millennia separates us from the Classical period of ancient Greece. Nevertheless, looking at ancient Greek medicine from the perspective of modern health economics is an interesting endeavour in that it increases our understanding of the ancient world and provides insights into contemporary society. Ancient Greece is rightly famous for pioneering secular and scientific medicine, but equally noteworthy is the prominence of healing cults, such as that of Asklepios. In this paper, the market for secular physicians is illuminated with tools from modern economics, for example the concern for the physician's reputation. The simultaneous emergence in ancient Greece of a scientific and rational approach to medicine and the proliferation of religious medicine provides an interesting vantage point for a study of the current market for alternative medicine. Similar circumstances arguably lie behind the dual nature of the health market that was present then and is still present now. The underlying mechanism in both periods is hypothesised to be increased uncertainty in everyday life.
Keywords: I11; N33; 330; health; economics; medicine; ancient Greece; alternative